Comparison of demographics, disease characteristics, and outcomes between Black and White patients with myelodysplastic syndromes: A population-based study. (February 2023) - Lesegretain, Arnaud; Brunner, Andrew; King, Andrew J.; Laadem, Abderrahmane; Fell, Geoffrey; Fathi, Amir T.
Abstract: Racial disparities in cancer care and outcomes have been well documented in various malignancies, with Black patients having the highest death rate and shortest survival of any racial/ethnic group in the United States (US) for most cancers. However, there have been limited studies on racial/ethnic disparities in myelodysplastic syndromes (MDS). Our study characterized and compared differences in baseline demographics, clinical characteristics, socioeconomic factors, and overall survival (OS) between Black and White patients with MDS in the US. We used the Surveillance, Epidemiology, and End Results (SEER) Program and included 37, 562 patients (Black, 8.1 %; White, 91.9 %) diagnosed between 2001 and 2013. We observed significant differences in baseline characteristics between cohorts. In a univariate analysis, Black race was associated with longer survival (hazard ratio [HR]: 0.83; 95 % confidence interval [CI], 0.79–0.86; p  < 0.001). The association between race and survival was attenuated but remained significant in various models to adjust for differences in baseline characteristics (HR in multivariable analysis, 0.92; 95 % CI, 0.87–0.96); p < 0.001). Subgroup analysis by histology revealed differences in the association between race and OS. Refractory anemia (RA), RA with ring sideroblasts, and MDS–not otherwise specified, a category in SEER representing a poorly defined MDS subset for 52 % of cases in our study, favored Black patients. RA with excess blasts favored White patients. The overall finding that Black race is associated with better OS outcomes, when compared with White patients, needs to be interpreted with caution and nuanced by histology. Additional research to explore these associations is warranted. Highlights: SEER analysis found Black race associated with longer survival in patients with MDS. This association was impacted by MDS histology and metropolitan residential status. Results should be interpretated with caution due to known limitations of SEER data. Results may be driven by a high proportion of MDS–not otherwise specified subset. We confirmed that CVD is a common cause of death in patients with MDS.